2016
DOI: 10.1371/journal.pone.0153018
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cell Composition in Renal Cell Carcinoma

Abstract: PurposeDue to their minimal-invasive yet potentially current character circulating tumor cells (CTC) might be useful as a “liquid biopsy” in solid tumors. However, successful application in metastatic renal cell carcinoma (mRCC) has been very limited so far. High plasticity and heterogeneity of CTC morphology challenges currently available enrichment and detection techniques with EpCAM as the usual surface marker being underrepresented in mRCC. We recently described a method that enables us to identify and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 45 publications
(43 reference statements)
2
29
0
Order By: Relevance
“…Through the studies for metabolomics, many promising candidates of a biomarker for RCC that were useful not only for early detection, but also the prediction of the effects of therapeutic agents and prognosis, have been identified. 115 Consistent with other malignant diseases, upregulation of aerobic glycolysis and the increase of some metabolites related to glycolysis, such as glucose, pyruvate and lactate, are shown in RCC patients. 116 In contrast, downregulation of the tricarboxylic acid cycle, an increase of citrate and succinate, and a decrease of fumarate and malate have been reported.…”
Section: Ctcssupporting
confidence: 58%
See 1 more Smart Citation
“…Through the studies for metabolomics, many promising candidates of a biomarker for RCC that were useful not only for early detection, but also the prediction of the effects of therapeutic agents and prognosis, have been identified. 115 Consistent with other malignant diseases, upregulation of aerobic glycolysis and the increase of some metabolites related to glycolysis, such as glucose, pyruvate and lactate, are shown in RCC patients. 116 In contrast, downregulation of the tricarboxylic acid cycle, an increase of citrate and succinate, and a decrease of fumarate and malate have been reported.…”
Section: Ctcssupporting
confidence: 58%
“…In oncological research, metabolomics approaches have been focused, and metabolomics reprogramming has been recognized as a crucial point of cancer biology. Through the studies for metabolomics, many promising candidates of a biomarker for RCC that were useful not only for early detection, but also the prediction of the effects of therapeutic agents and prognosis, have been identified …”
Section: Other Candidates Of Biomarkersmentioning
confidence: 99%
“…While several studies report detection and characterization of CTCs in tumor entities including breast or prostate cancer, the number of reports describing CTC detection in clear cell renal cell carcinoma (ccRCC) patients is limited. Most initial studies describe whole blood nucleic acid extraction and analysis [ 11 16 ] or CD45-negative selection [ 6 , 14 16 ]. In a comparison of different tumor entities using the CellSearch system, ccRCC showed the lowest frequency of CTCs compared to all other tumor entities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bluemke discovered that positive CK+ CTCs was significantly correlated with inferior overall survival for renal cancer patients [13]. Nel found that the presence and quantity of CD133-positive or N-cadherin-positive CTC was associated with poor PFS in 14 renal cancer patients [27]. Due to the relative short follow-up time and relative early stage of patients, 15.3% patients (20/131) experienced recurrence or metastasis in our study.…”
Section: Discussionmentioning
confidence: 54%